EFFECT OF EVAPORATION ON C7 LIGHT HYDROCARBON PARAMETERS - Canipa-Morales N.K.; Galan-Vidal C.A.; Guzman-Vega M.A.; Jarvie D.M. (My University, 2003)
Light hydrocarbons are commonly used to evaluate crude oils to determine oil families, in-reservoir alteration processes such as evaporative fractionation, water washing, incipient biodegradation, maturity, and temperatures at which oil is expelled from source rocks. Light hydrocarbons in the C7 range will evaporate under ambient conditions, and losses can occur during sample collection, handling, or storage. However, the impact of partial evaporation on interpretation of light hydrocarbon data has not been reported previously. Laboratory evaporation experiments show that the rate of evaporation of each C7 hydrocarbon is different, and these differential rates will affect the measured concentrations of these compounds, certain ratios, and other calculations or plots using these data. The paraffinicity/aromaticity ratio of Thompson [Marine Pet. Geol. 5 (1988) 237], parameters utilized in the transformation and correlation star diagrams of Halpern [AAPG Bull. 79 (1995) 801], and the oil typing ternary plot of Jarvie [The Mountain Geologist 38 (2001) 19] are affected by evaporation. Other interpretive schemes such as P2 versus N2/P3 and the invariant ratio [Science 273 (1987) 514; Geochim. Cosmoschim. Acta 54 (1990) 1315] are not grossly affected by partial evaporation because these parameters are primarily controlled by the concentration of methylhexanes or by offsetting rates of evaporation in certain compounds. By careful evaluation of these parameters and various interpretive plots, the extent of evaporation can be qualitatively assessed and discrimination of oil types, alteration effects, and evaporative artifacts can still be reasonably ascertained. This study demonstrates that preservation of crude oils from evaporation is essential for accurate application of all light hydrocarbon parameters, although some parameters may still be utilized when partial evaporation has occurred.